RURAL SETTLEMENTS POPULATION NUMBER REGIONAL FEATURES AND CURRENT PROBLEMS IN THE RA BORDERING BELT (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
Population number reflects the cumulative impact of several factors on the development of rural areas and settlements. Besides, settlement transformation and development processes are essentially conditioned by population number of rural settlements and population distribution by population number. In the bordering belt of the RA the function of fortifying and strengthening the self-defense of the country joins the mentioned ones. The RA bordering belt rural settlements population number and rural population regional distribution by population number features analysis and current problems revelation have been done in the article.
Keywords: rural settlements; population number; regional features; prevailing population number; elevation zones; current problems